2014
DOI: 10.1177/0192512114543160
|View full text |Cite
|
Sign up to set email alerts
|

Why do some governments resort to ‘creative accounting’ but not others? Fiscal governance in the Brazilian federation

Abstract: This paper investigates the determinants of compliance with fiscal rules. Using information from 27 Brazilian state governments, the paper shows that the level of political competition and the degree of political autonomy of the fiscal watchdogs explain the extent of creative accounting in the Brazilian federation. Despite hard budget constraints imposed by the much-acclaimed Fiscal Responsibility Law, state governors retain the strategic ability to undertake fiscal window dressing in response to fiscal stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The inclusion of this category is motivated by the debate among academics and practitioners about public-sector accounting and accountability (Manes-Rossi et al, 2020), which has shown that academic research has had a moderate impact on accounting practices (Steccolini, 2019). Indeed, the results emerging from the analysis (Figure 12) support the idea of such a limited influence, as 73 out of the 78 articles (about 94%) were written by academics, while only four articles (von Hagen and Wolff, 2006;Cheng et al, 2010;Melo et al, 2014;Kartiko et al, 2018) were written by a team that included at least one practitioner.…”
Section: Authorsmentioning
confidence: 89%
“…The inclusion of this category is motivated by the debate among academics and practitioners about public-sector accounting and accountability (Manes-Rossi et al, 2020), which has shown that academic research has had a moderate impact on accounting practices (Steccolini, 2019). Indeed, the results emerging from the analysis (Figure 12) support the idea of such a limited influence, as 73 out of the 78 articles (about 94%) were written by academics, while only four articles (von Hagen and Wolff, 2006;Cheng et al, 2010;Melo et al, 2014;Kartiko et al, 2018) were written by a team that included at least one practitioner.…”
Section: Authorsmentioning
confidence: 89%
“…The results of the research can be explained by the institutional limitations to the performance of the Courts of Account in the control of the rules concerning expenses. Melo, Pereira, and Souza (2014) associate the existence of a "fiscal creativity" to the institutional fragilities of the Courts of Account by exposing them to the pressure from local executive and legislative branches. One of such fragilities would be the absence of council members at full bench sessions who are selected by exams.…”
Section: Figure 3 Limits Of the Expense With Personnel In 2018mentioning
confidence: 99%
“…Lack of uniformization as to how to assess expenses with personnel not only impairs any comparability between balance sheets -especially the Fiscal Management Report -, but it also allows some Courts of Account to increase their own limit to expenses with personnel based on the methodology they apply by avoiding to resort to the adjustment measures set under the LRF. Nunes et al (2019) and Melo et al (2014) identified other divergences in the interpretations of such external control organs, which allow the record of the remaining payable balance over the cash flow available at the end of any tenure (in breach of section 42 of the LRF), or which were permissive with administrations failing to comply with their fiscal targets. The aforementioned authors state as the main justification the political interest of council members in courts who do not wish to harm local legislative or executive branches.…”
Section: Closing Argumentsmentioning
confidence: 99%